2016
DOI: 10.1007/s12253-016-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Repair Genes Polymorphisms in Breast Cancer

Abstract: Genetic polymorphisms in the DNA repair genes may be associated with increased cancer risk. The purpose of this study was to evaluate the association of the DNA repair genes polymorphisms with the risk of breast cancer development. The study included 200 breast cancer patients and 200 healthy controls. The following polymorphisms were studied: C/G (Ser326Cys, rs1052133) of the hOGG1, A/C (IVS5 + 33, rs3212961) of the ERCC1, A/C (Lys939Gln, rs2228001) of the XPC, C/T (Thr241Met, rs861539) of the XRCC3, G/T (Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…The SNPs rs11615 and rs3212961 in ERCC1 have strong or moderate linkage disequilibrium in Asian and European populations [ 49 ] and may be a significant haplotype. Our pooled results provide strong evidence of the increased risk of breast cancer for ERCC1 rs11615, and Romanowicz et al [ 9 ] concluded that Caucasian populations with the CC genotype of ERCC1 rs3212961 have 10.61-times the risk of developing breast cancer. Thus, certain haplotypes may increase the strength of an individual polymorphism and lead to significant enrichment of essential biological functions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The SNPs rs11615 and rs3212961 in ERCC1 have strong or moderate linkage disequilibrium in Asian and European populations [ 49 ] and may be a significant haplotype. Our pooled results provide strong evidence of the increased risk of breast cancer for ERCC1 rs11615, and Romanowicz et al [ 9 ] concluded that Caucasian populations with the CC genotype of ERCC1 rs3212961 have 10.61-times the risk of developing breast cancer. Thus, certain haplotypes may increase the strength of an individual polymorphism and lead to significant enrichment of essential biological functions.…”
Section: Discussionsupporting
confidence: 69%
“…Genomic instability is a potential carcinogenic factor; organisms have developed an elaborated set of DNA repair systems involving multiple sophisticated mechanisms for repairing an extremely broad array of DNA lesions induced by internal and external stressors to maintain genome integrity and stability [ 7 , 8 ]. A series of proteins assemble and respond to DNA damage in a stepwise fashion in these pathways, and the alteration of genes encoding such proteins undoubtedly contributes to the variability of the more directly implicated genes and may therefore be significantly related to the risk of cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A huge meta-analysis has shown that this SNP provides slight but statistically significant BrC risk increase [64], mainly due to altered protein function, increased genetic instability and DNA DSB accumulation [23]. Recently performed studies on Polish population, however, failed to confirm such effect on either unselected or triple-negative BrC [32,33]. It has to be, however stated, that these two Polish studies, alike the hereby presented one, were relatively small in their sizes (up to 200 BrC subjects only), thus the effect revealed by a meta-analysis involving almost 10,000 BrC cases may have not simply been provable.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of BrC among carriers of the 241 Met-containg genotypes was found to be increased compared to wild-type carriers by some 6-10% under various genetic models [29][30][31]. Nevertheless, recent smaller studies conducted in Polish BrC population failed to provide evidence on any unambiguous effect with respect to BrC risk [32,33]. Other studies proposed the 17893 G allele (rs1799796; intron 7; c.562-14A>G; 17893 A/G) as providing protective effect against BrC (risk reduction of some 10%) [31].…”
Section: Introductionmentioning
confidence: 99%
“… 72 , 73 , 84 87 However, studies also have found no association of XRCC3 ( Thr241Met ) gene with the risk of BC and thus compelled to hypothesize that ethnic variation also persists between XRCC3 ( Thr241Met ) polymorphism and the risk of BC in females. 38 , 40 , 88 90 However, It has been assumed that XRCC3 ( Thr241Met ) is an important candidate gene in tumorigenesis. 91 Thus, to investigate the association of XRCC3 ( Thr241Met ) polymorphism with the increased risk of BC in females from NE region of India, we carried out both univariate and multivariate logistic regression analyses after adjustment for reproductive factors and food habits.…”
Section: Discussionmentioning
confidence: 99%